Research for Fire Prevention Management in Indonesia (Smoke, Haze, GHG Emission Reduction, and Deforestation) - Bambang Hero Saharjo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Forest and land fires, not only in Indonesia but also in other parts of the world, have actually caused tremendous negative impacts. It causes negative impact to the environments (smoke, haze), social, education, health, flora and fauna, state life, and so on that are sourced from most human activities, which have an impact on global climate change. The negative impacts of forest and land fires must be controlled through serious and systematic control of forest and land fires and supported by the political will of the government. It should be understood that forest and land fire control activities should be based on the field facts derived from research results and not based on fictitious results or temporary estimates. Research efforts can also be expected through regional and international cooperation. Keywords: Forest, fires, research, climate change, collaboration